Commerical Policy and Its Scientific Method: A Reply - Eulenburg, F. (Quarterly Journal of Economics, 1930)
Journal Article Commercial Policy and Its Scientific Method: A Reply Get access F. Eulenburg F. Eulenburg Handelshochschule, Berlin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 4, August 1930, Pages 698–706, https://doi.org/10.2307/1884031 Published: 01 August 1930